Musculus multifidus makes provisions to posterolateral spine fusion after transpedicular fixation of lumbar spine - Radchenko, Volodymyr; Skidanov, Artem; Ashukina, Nataliya; Danyshchuk, Zinaida; Nessonova, Marina; Morozenko, Dmytro; Skidanov, Nikita (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Disturbances of structure and function of paravertebral muscles are one of the risk factors of lumbar spine degenerative diseases. It is proved that muscles play an important role in spine fusion and in other bones fusion. Objective: to analyze the relationship between the results of the posterolateral lumbar fusion after stabilization of LIV–LV vertebrae with the use of transpedicular screws and structural features of m. multifidus caused by different levels of physical activity. Methods: 20 laboratory rats were divided in four groups, each of five animals: І — have swum before and after surgery; ІІ — have swum before surgery only; IІІ — have swum after surgery only; ІV — have not swum. All animals underwent posterolateral spinal fusion, transpedicular construction was mounted at LIV–LV level. X -ray examination was performed directly after surgical procedure, and 3 months later. Histologic study was performed for evaluating of m. multifidus and spine fusion area. Results: using X-ray examination the signs of formed posterior spine fusion were observed 3 months after operation in 80 % animals of I group, in 60 % of II, in 40 % of III, in 20 % of IV. Histologically it was established that the degree of muscles changes directly correlates with the quality of spine fusion. Minimal signs of muscle fibers destructive changes, as well as maximum observations of formed spine fusion, were registered in the I group under increased physical activity regimen, while most evident destructive changes and the worst results — in IV group with low physical activities. We have established weak but statistically significant correlations between increased physical activity and reduction of the content of adipose (р = 0.010512) and fibrous (р = 0.019142) tissue in the muscles of operated rats. Conclusion: physical activity has a positive influence upon functional and adaptive muscle capacity and forming of posterior spine fusion.